Application of Problem Based Learning Model to Mathematical Thinking Ability - Ernawati Ernawati; Rahmawati Rahmawati (EduMa: Mathematics education learning and teaching, 2021)
This research is a pre-experimental research that aims to determine differences in the mathematical critical thinking skills of class VIII students of MTs Hj. Haniah before and after the application of the problem based learning model. The design of this research is quantitative research with one group pretest-posttest design, the population in this study were students of class VIII MTs Hj. Haniah with samples taken randomly or simple random sampling, namely class VIII A with a total of 21 students. The data were collected using a test of students' mathematical critical thinking skills and an observation sheet on the implementation of the learning model that has been validated by the expert. The research data were analyzed descriptively and inferential with the normality test as the prerequisite test for analysis and paired sample t-test as the hypothesis test. The results of data analysis showed that the mean pre-test was 51.9 while the post-test mean was 74.14. Based on the paired sample t-test, the significant value was 0.000<Î±= 0.025 . The results of this study indicate that there are differences in the mathematical critical thinking skills of class VIII students of MTs Hj. Haniah between before and after the problem-based learning model is applied to the material pattern and object navigation